Inequalities in colorectal cancer diagnosis by ethnic group: a population-level study in the English National Health Service - Amy Downing; Mo Thoufeeq; James Turvill; Eva J A Morris; Phil Quirke; John C Taylor; Rebecca J Birch; Nick E Burr (BMJ Open Gastroenterology)
Objective Studies in the USA examining the relationship between ethnicity and colorectal cancer (CRC) identified significant variation. This study sought to examine the relationship between ethnic group, route to diagnosis, early-onset CRC and stage at diagnosis in the English National Health Service.Methods Data from COloRECTal cancer data Repository for all individuals diagnosed with CRC (International Classification of Diseases version 10, C18–C20) between 2012 and 2017. A descriptive analysis of the characteristics of the study population was performed. Multivariable logistic regression models were used to assess the association between ethnicity, route to diagnosis, stage at diagnosis and early-onset CRC.Results Early-onset CRC was least common in those in the white ethnic group (5.5% diagnosed <50, vs 17.9% in the Asian, 15.5% in the black and 21.8% in the mixed and multiple ethnic groups, p<0.01). Diagnosis following a 2-week wait referral was significantly less common among individuals from the Asian, black, other and unknown ethnic groups than the white ethnic group (Asian OR 0.84, 95% CI 0.79 to 0.91, black OR 0.86, 95% CI 0.79 to 0.93, other OR 0.81, 95% CI 0.73 to 0.90 and unknown OR 0.70, 95% CI 0.66 to 0.73). The Asian ethnic group had significantly lower odds of emergency diagnosis than the white ethnic group (OR 0.90, 95% CI 0.83 to 0.97). Following adjustment, individuals from the Asian ethnic group were significantly less likely, than their white counterparts, to be diagnosed at stage IV (OR 0.82, 95% CI 0.76 to 0.88).Conclusion This study identified different demographic profiles of those diagnosed with CRC between broad ethnic groups, highlighting the need to consider access to diagnostic CRC services in the context of ethnicity.